Evaluation of three formulations based on Polymorphic membrane protein D in mice infected with Chlamydia trachomatis - Russi, Romina Cecilia; del Balzo, Diego; Reidel, Ivana Gabriela; Alonso Bivou, Mariano; Flor, Noelia; Lujan, Agustín; Sanchez, Diego; Damiani, María Teresa; Veaute, Carolina (Frontiers in Immunology, 2023)
The significant impact of Chlamydia trachomatis (Ct) infections worldwide highlights the need to develop a prophylactic vaccine that elicits effective immunity and protects the host from the immunopathological effects of Ct infection. The aim of this study was to evaluate a vaccine based on a fragment of the Polymorphic membrane protein D (FPmpD) of C. trachomatis as an immunogen using a heterologous DNA prime-protein boost strategy in female mice Three different formulations were evaluated as protein boost: free recombinant FPmpD (rFPmpD) or rFPmpD formulated with a liposomal adjuvant alternatively supplemented with CpG or a cationic gemini lipopeptide as immunostimulants. The three candidates induced an increase in the cervicovaginal and systemic titers of anti-rFPmpD antibodies in two strains of mice (BALB/c and C57BL/6), with no evidence of fertility alterations. The three formulations induced a rapid and robust humoral immune response upon the Ct challenge. However, the booster with free rFPmpD more efficiently reduced the shedding of infective Ct and prevented the development of immunopathology. The formulations containing adjuvant induced a strong inflammatory reaction in the uterine tissue. Hence, the primeboost strategy with the adjuvant-free FPmpD vaccine formulation might constitute a promissory candidate to prevent C. trachomatis intravaginal infection.